Clash of the Titans: Temporal Organizing and Collaborative Dynamics in the Panama Canal Megaproject. Issue 12 (December 2016) - van Marrewijk, Alfons; Ybema, Sierk; Smits, Karen; Clegg, Stewart; Pitsis, Tyrone
Recent studies of temporary organizing and project-based work explain how organizational actors establish and maintain clear role structures and harmonious relations in the face of precariousness by engaging in stabilizing work practices. This focus upon 'order' undervalues conflict-ridden negotiations and power struggles in temporary organizing. This paper demonstrates that in temporary organizing conflict and order may exist in tandem. Drawing close to the collaborative dynamics in a large-scale global project, we analyse the political struggles over role patterns and hierarchic positioning of client and agent in the temporary organization of the Panama Canal Expansion Program (PCEP). In such projects, the agent typically takes the position of project leader. In this case however, the client was formally in charge, while the agent was assigned the role of coach and mentor. The diffuse hierarchy triggered project partners to engage in both harmony-seeking social and discursive practices and to enter into conflict-ridden negotiations over authority relations in the everyday execution of the PCEP project. Our study contributes to existing literatures on temporal organizing by presenting a case of simultaneous practices of harmonization and contestation over mutual roles and hierarchic positions. We also show that studying collaboration between project partners involves, not merely analysing project governance structures, but also offering a context-sensitive account of everyday social and discursive practices. Finally, we reflect on a view of 'permanence' and 'temporariness' as themselves contested categories and symbolic sites for struggle.